Unveiling the Launaea nudicaulis (L.) Hook medicinal bioactivities: phytochemical analysis, antibacterial, antibiofilm, and anticancer activities - Elkady, Fathy M.; Badr, Bahaa M.; Hashem, Amr H.; Abdulrahman, Mohammed S.; Abdelaziz, Amer M.; Al-Askar, Abdulaziz A.; AbdElgayed, Gehad; Hashem, Hany R. (Frontiers in Microbiology, 2024)
Commonly used antimicrobial agents are no longer effective due to their overuse or misuse. In addition, many medicinal plant extracts can combat infectious diseases due to their main active constituents or secondary metabolites. The current study aimed to assess the bioactivities of Launaea nudicaulis (LN) leaf extract (LE) against different multi-drug resistant (MDR) Pseudomonas aeruginosa (P. aeruginosa) isolates. The ethyl acetate extract of a Launaea nudicaulis (LN) leaf was analyzed using GC–MS, which identified 27 key bioactive compounds. The major constituents found were as follows: 7-acetyl-6-ethyl-1,1,4,4-tetramethyltetralin, isopropyl myristate, thiocarbamic acid, N,N-dimethyl, S-1,3-diphenyl-2-butenyl ester, hahnfett, cyclopentane acetic acid, 3-oxo-2-pentyl-, methyl ester, hexadecanoic acid, and dotriacontane. Our study demonstrated that the LN leaf was a rich source of other important phytochemicals, including phenolic acids, tannins, saponins, and steroids. The relative biosafety of the L. nudicaulis LE was determined from the elevated inhibitory concentration 50 (IC50) of 262 μg/mL, as calculated from the cytotoxicity assay against the Wi-38 normal cell line. Conversely, 12.7 and 24.5 μg/mL were the recorded low IC50 values for the tested extract against the MCF-7 and Hep-G2 cancerous cell lines, respectively, reflecting its potent activity against the tested cancerous cell lines. Microbiologically, the susceptible P. aeruginosa isolates to the tested extract showed a growth inhibition zone diameter, in the well diffusion assay, ranging from 11.34 ± 0.47 to 26.67 ± 0.47 mm, and a percent inhibition (PI) value of 50–106.2%, reflecting its acceptable activity. In addition, the broth microdilution assay recorded minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) in the ranges of 15.625–1,000 μg/mL and 125–1,000 μg/mL, respectively. In conclusion, the L. nudicaulis LE revealed showed promising activity and high selectivity against P. aeruginosa. Moreover, the extract exhibited natural anticancer activities with safe low concentrations, indicating its potential as a superior candidate for future studies of its active constituents.